Clinical Competence of Nurses and the Associated Factors in Public Hospitals of Gamo Zone, Southern Ethiopia: A Cross-Sectional Study - Shitaye Shibiru; Zeleke Aschalew; Mekidim Kassa; Agegnehu Bante; Abera Mersha (Nursing Research and Practice)
Introduction. Nursing competency is an essential component for improving the quality of care in the healthcare system. However, assessing competency solely on the dimensions of skills and knowledge does not provide complete picture of a nurse ability to provide quality patient care. This is because it lacks focus on the nurse’s attitudes and values, which are also important determinants of clinical competence. Therefore, this study aimed to assess the comprehensive clinical competence of nurses and its associated factors in public hospitals of Gamo Zone, Southern Ethiopia. Materials and Methods. A cross-sectional study was conducted using a census method to collect information from nurses through self-administered questionnaires. The data were entered into EpiData version 3.1 and exported to Stata version 15 for analysis. A linear regression model was used to identify factors associated with clinical competence. Results. In this study, the average clinical competence of nurses was 177.32, with a standard deviation of 19.19, and 31.2% of the respondents had a high level of clinical competence. Associated factors identified with clinical competence include gender, age, marital status, qualification, position, work experience, unit, interest in their profession, critical thinking disposition, clinical self-efficacy, and emotional intelligence. Conclusions. The overall level of clinical competence among nurses in this study was moderate. As such, nurses improve their clinical competence by receiving training and development opportunities that focus on critical thinking, clinical self-efficacy, and emotional intelligence; working in a supportive work environment that encourages them to take risks and learn from their mistakes; and being monitored and coached on a regular basis.